A clinical case of partial hypopituitarism - T. E. Pomytkina (Фундаментальная и клиническая медицина)
Here we present current data on epidemiology, mechanisms of development, and clinical symptoms of pituitary insufficiency ascribing a case of a 27-year-old woman who became pregnant and successfully delivered with a partial hypopituitarism without a hormone replacement therapy. We particularly focus on the difficulties in timely diagnosis of pituitary insufficiency, as partial hypopituitarism is characterised by a variety of non-specific symptoms. A particular attention should be drawn to the physicians’ awareness on partial hypopituitarism, as its case fatality rate remains unacceptably high.